Eosinophils and Purinergic Signaling in Health and Disease - Ferrari, Davide; Vuerich, Marta; Casciano, Fabio; Longhi, Maria Serena; Melloni, Elisabetta; Secchiero, Paola; Zech, Andreas; Robson, Simon C.; Müller, Tobias; Idzko, Marco (Frontiers in Immunology, 2020)
Eosinophils are major effector cells against parasites, bacteria and viruses. However, these cells also take part in local and systemic inflammation, which are central to eczema, atopy, rhinitis, asthma and autoimmune diseases. A role for eosinophils has been also shown in vascular thrombotic disorders and in cancer. Many if not all, above-mentioned conditions involve the release of intracellular nucleotides (ATP, ADP, UTP, etc.) and nucleosides (adenosine) in the extracellular environment. Simultaneously, eosinophils further release ATP, which in autocrine and paracrine manners, stimulates P2 receptors. Purinergic signaling in eosinophils mediates a variety of responses including CD11b induction, ROI production, release of granule contents and enzymes, as well as cytokines. Exposure to extracellular ATP also modulates the expression of endothelial adhesion molecules, thereby favoring eosinophil extravasation and accumulation. In addition, eosinophils express the immunosuppressive adenosine P1 receptors, which regulate degranulation and migration. However, pro-inflammatory responses induced by extracellular ATP predominate. Due to their important role in innate immunity and tissue damage pharmacological targeting of nucleotide- and nucleoside-mediated signaling in eosinophils could represent a novel approach to alleviate eosinophilic acute and chronic inflammatory diseases. These innovative approaches might also have salutary effects, particularly in host defense against parasites and in cancer.